TINDAK PIDANA PENYEBARAN ELEKTRONIK YANG BERMUATAN MELANGGAR KESUSILAAN TERHADAP WANITA DIBAWAH UMUR - Cahyorini Laksitowati; Amir Junaidi; Ida Aryati Dyah Purnowo Wulan (GEMA, 2022)
One type of crime that is growing rapidly today is crime committed electronically, or what is known as cybercrime. This crime takes many forms. These crimes take many forms. The presence of Law Number 11 of 2008 concerning Information and Electronic Transactions has regulated prohibited acts related to electronic information and transactions. There are various forms of cyber crime: Computer fraud (computer fraud), Criminal acts of embezzlement, falsification of providing information via a computer that harms other parties and benefits oneself, Hacking, Criminal acts of communication, Criminal acts of destroying computer systems, either damaging data or deleting codes that cause damage and loss, criminal acts related to intellectual property rights, copyrights and patents. And from cyber crime, children and women are the most vulnerable group to cyber crime.